University Students’ Persistence With Technology-Mediated Distance Education: A Response to COVID-19 and Beyond in Zimbabwe - Rudhumbu, Norman (International Review of Research in Open and Distributed Learning, 2021)
Technology-mediated distance education (TDE) has become part of the new normal in the range of teaching strategies used in universities in Zimbabwe. Contemporary literature abounds with studies that highlight challenges associated with access to education in universities, yet very little is highlighted about how TDE can be used to enhance access to education in Zimbabwean universities during the COVID-19 era and beyond. The purpose of this study was therefore to investigate determinants of students’ behavioural intentions to persist with TDE in universities in Zimbabwe during COVID-19 and beyond. The study employed a quantitative approach that used a self-constructed structured questionnaire for data collection from a sample of 1,300 distance learning students selected from five universities using a stratified random sampling strategy. Structural equation modelling using IBM SPSS Amos 22 was used for data analysis. Results of the study show that cultural and norms issues (β = .325; p < .001) and characteristics of the students (β = .329; p < .001), the lecturer (β = .362; p < .001), the institution (β = .427; p < .001), and external stakeholders (β = .279; p < .001) were all significantly associated with the behavioural intentions of university students to persist with TDE. Results of this study have implications for both policy and practice with regard to implementing TDE in universities.